Reliable Detection of Rotor Faults in IM Using Frequency Tracking and Zero Sequence Voltage - Khalid Dahi (Advances in Electrical and Electronic Engineering, 2017)
The AC Alternating Current Induction Motor (IM) is the most commonly used AC motor in industrial applications because of its simplicity, robust construction, and relatively low manufacturing costs. To avoid expensive repairs in IM, early faults detection is needed. In this context, this paper presents a novel approach used to detect rotor asymmetries in induction motors. The Zero Sequence Voltage (ZSV) defined as the potential difference between the null point of the supply voltage system and the neutral of the star connection of IM stator winding is measured and employed for tracking the amplitude of the most sensitive harmonics in the spectrum of ZSV. This detection leads to make a criterion to take a decision about the state of the machine without a Prior knowledge. Simulation and experimental results obtained from real tests are presented to validate the study.